Sistem Informasi Manajemen Aset Barang dan Kendaraan dengan Fitur Pengingat Otomatis Service dan Pajak Berbasis Mobile Web pada AMIK Luwuk Banggai - Indra Prayudi Sohat; Piktor Maatu; Sadam Sadam; Ishak Mangadang; Lutfi Saikim; Trisno Wibowo. K; I Gusti Putu Rika Permana (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
The management of goods and vehicles assets in an institution requires an effective system so that the process of recording, tracking, and maintaining assets can be carried out in a structured and efficient manner. AMIK Luwuk Banggai still faces obstacles in remembering periodic service schedules and vehicle tax payments, because the reminder process is still carried out manually and relies on conventional records. This poses a risk of maintenance delays and administrative fines due to late tax payments. Therefore, this research is focused on the design and development of a web-based goods and vehicle asset management information system equipped with automatic notification features through Telegram Bot integration. The system development in this study uses the Waterfall approach which includes the stages of needs analysis, system design, implementation, testing, and maintenance. Research data was obtained through interview methods with the management, observation of the running process, and literature review from various sources related to information systems and automatic notification technology. The system built utilizes mobile web technology to be easily accessible through mobile devices, as well as supporting work efficiency with a simple and responsive interface. The test results show that the system is able to provide real-time automatic notifications regarding maintenance service schedules and vehicle tax payment dues. Integration with Telegram Bot has proven to be effective in increasing the speed of information delivery, reducing the risk of delays, and giving users the flexibility to receive reminders on platforms that are familiar with everyday use. In addition, the implementation of the system also improves the overall efficiency of asset management because every asset information can be well documented, easily tracked, and integrated in a single platform.